Bakti Sosial: UMKM Bangkit dari Pandemi COVID-19 - Istinganah Eni Maryani; Mugi Harsono; Zandra Dwanita Widodo; Muhad Fatoni; Andi Yusuf Katili; Rini Adiyani; Syahri Alhusin (Rengganis Jurnal Pengabdian Masyarakat, 2022)
Covid-19 pandemic impacts all aspects of Indonesians’ life. In 2021 MSMEs and street sellers in Jaten neighborhood, Karanganyar, Central Java affected by the pandemic are out of business. Some social-economic phenomena occur in which people lose their livelihood and people’s purchasing interest decreases affecting certain product and service commodities. Although the people are now adapting to new normal life, economic activities of MSMEs are still starting to get up. Responding to those conditions, we, a community service team consisting of the collaboration between academic communities, hold social service through distributing food staple packages to the MSME actors needing. The community service method used was participatory approach by involving the lecturers and students to distribute directly the food staple packages to the MSME actors in Jaten neighborhood, Karanganyar, implemented on independent initiative in Ramadhan month in 2021 for one day as scheduled. The distribution of food staple packages has run well and smoothly according to health protocol as appealed by the government. This community service activity is expected to relieve the burden of MSME actors who are affected directly by Covid-19 pandemic. This community service is supported fully by local village apparatuses, lecturers, and students involved, so that this activity can be implemented well.